Meningkatkan Pengetahuan Pendidikan Seks Siswa melalui Layanan Informasi - Dewi, Desy Mustika; Kurniawan, Kusnarto (Universitas Negeri Semarang, 2016)
This study was conducted based on the phenomenon that occurs in Islamic Elementary fifth grade students of State Sumurrejo Semarang who display symptoms of low deviant behavior related to sex education knowledge. The purpose of this study was to change the level of students' knowledge of sex penddikan through information services. This type of research is experimental research. Experimental research is research used to search for a specific treatment effect. This study was conducted with eight times giving treatment at Government Elementary School sixth grade students of State Sumurrejo Semarang, the research subjects 23 students. Data collection methods used were a test of knowledge of sex education. Data were analyzed using descriptive analysis of the percentage and the Wilcoxon test. The results showed knowledge of sex education 39% of students categorized as low. After being given a treatment through information services increased knowledge of sexual education of students in the high category 75%. It shows that information services affect the increase students' knowledge is sex education.